Limonoids and flavonoids from the flowers of Azadirachta indica var. siamensis, and their melanogenesis-inhibitory and cytotoxic activities - Worapong Kitdamrongtham (2018)
A new limonoid, 7-O-acetyl-7-O-debenzoyl-22-hydroxy-21-methoxylimocinin (2), and two new flavonoids, 3′-(3-hydroxy-3-methylbutyl)naringenin (7) and 4′-O-methyllespedezaflavanone C (9), along with nine known compounds, including two limonoids, 1 and 3, and seven flavonoids, 4-6, 8, and 10-12, were isolated from a MeOH extract of the flowers of Azadirachta indica A.Juss. var. siamensis Valeton (Siamese neem tree; Meliaceae). The structures of new compounds were elucidated on the basis of extensive spectroscopic analysis and comparison with literature data. All of these compounds were evaluated for their melan ogenesis-inhibitory activities in B16 melanoma cells induced with α-melanocyte-stimulating hormone (α-MSH). Compound 2 (16.9% melanin content at 30 μM), 6-deacetylnimbin (3; 49.6% melanin content at 100 μM), and kaempferide (10; 41.7% melanin content at 10 μM) exhibited inhibitory effects with no, or almost no, toxicity to the cells (81.0-111.7% cell viability). In addition, evaluation of their cytotoxic activities against HL60, A549, AZ521, and SK-BR-3 human cancer cell lines, isoazadironolide (1), 4′-O-methyl-8-prenylnaringenin (5), euchrestaflavanone A (8), 9, and 3-methoxy-3′-prenylnaringenin (12) revealed potent cytotoxicities against one or more cell lines with IC 50 values in the range of 4.5-9.9 μM. Copyright © 2014 Verlag Helvetica Chimica Acta AG, Zürich.